Neuronal localization of the 5-HT2 receptor family in the amygdaloid complex - Bombardi, Cristiano (Frontiers in Pharmacology, 2014)
The amygdaloid complex (or amygdala), a heterogeneous structure located in the medial portion of the temporal lobe, is composed of deep, superficial, and “remaining” nuclei. This structure is involved in the generation of emotional behavior, in the formation of emotional memories and in the modulation of the consolidation of explicit memories for emotionally arousing events. The serotoninergic fibers originating in the dorsal and medial raphe nuclei are critically involved in amygdalar functions. Serotonin (5-hydroxytryptamine, 5-HT) regulates amygdalar activity through the activation of the 5-HT2 receptor family, which includes three receptor subtypes: 5-HT2A, 5-HT2B, and 5-HT2C. The distribution and the functional activity of the 5-HT2 receptor family has been studied more extensively than that of the 5-HT2A receptor subtypes, especially in the deep nuclei. In these nuclei, the 5-HT2A receptor is expressed on both pyramidal and non-pyramidal neurons, and could play a critical role in the formation of emotional memories. However, the exact role of the 5-HT2A receptor subtypes, as well as that of the 5-HT2B and 5-HT2C receptor subtypes, in the modulation of the amygdalar microcircuits requires additional study. The present review reports data concerning the distribution and the functional roles of the 5-HT2 receptor family in the amygdala.